Case Report: Pitfalls in anatomic pathology and clinical oncology: a case of misdiagnosed pulmonary Ewing sarcoma as SCLC - El Waary, Nagham S.; Chami, Angelo A.; Zrein, Jawad K.; Houcheimy, Doha A.; Akl, Ryan T.; Fleifel, Siham D.; Kamar, Francois G. (Frontiers in Oncology, 2025)
In oncology, an accurate pathological diagnosis can often mean the difference between cure and failure, potentially determining a patient’s survival. We present the case of a 28-year-old, never-smoking man whose initial diagnosis of small cell lung cancer (SCLC) was confirmed by the anatomic pathology laboratory upon reevaluation, despite initial doubt. This misclassification ultimately led to therapeutic failure following an initial complete remission and likely contributed to the poor outcome after the diagnosis was later corrected to pulmonary Ewing sarcoma. Primary pulmonary Ewing sarcoma is a rare malignancy that is often overlooked in adults. This case underscores not only the striking clinical and histopathological overlap between SCLC and pulmonary Ewing sarcoma but also the potentially fatal consequences of missing key diagnostic red flags, including the patient’s young age, non-smoking status, and atypical clinical course. Through this patient’s journey, we emphasize the importance of multidisciplinary collaboration, the limitations of relying solely on immunohistochemistry, and the critical role of early molecular testing. This case serves as a stark reminder that behind every pathology report is a human life—one that depends on the vigilance, humility, and thoroughness of the medical team entrusted with their care.